Short-term benefits of an unrestricted-calorie traditional Mediterranean diet, modified with a reduced consumption of carbohydrates at evening, in overweight-obese patients. (17th February 2017) - Salvia, Roberto; D'Amore, Simona; Graziano, Giusi; Capobianco, Caterina; Sangineto, Moris; Paparella, Domenico; de Bonfils, Paola; Palasciano, Giuseppe; Vacca, Michele
Abstract: The Mediterranean diet (MeD) is believed to promote health; nevertheless, changes in the nutritional patterns in the Mediterranean area (increased intake of refined carbohydrates/saturated fats; reduced fibers intake; main calorie load shifted to dinner) led to reduced MeD benefits in recent decades. We retrospectively investigated the effects of a MeD with a low intake of refined carbohydrates in the evening ("MeDLowC") on body weight (BW) and metabolic profile of overweight/obese subjects. According to their adherence to MeDLowC, subjects were classified into 44 (41%) individuals with "excellent" adherence and 63 (59%) with "poor" adherence. Nutritional counseling induced an improvement in BW, glucose metabolism and liver transaminases in both groups, with an increased magnitude of these effects in the "Excellent" adherence group. "Excellent" adherence to MeDLowC improved insulin sensitivity and lipid metabolism. In conclusion, MeD with a restriction of carbohydrates in the evening significantly ameliorates obesity and associated metabolic complications.